Human Assets Index Retrospective series: 2013 update - Michaël Goujon; Mathilde Closset; Sosso Feindouno (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
Human capital, a broad concept including education and health, plays a central role in economic development and human well-being. As a consequence, low human capital became one of the three criteria used by the United Nations Committee for Development Policy (UN-CDP) for identifying Least Developed Countries (LDCs). Since 1991, the UN-CDP has used a composite index to measure human capital at the country level. In 2003 this index was reshaped and was renamed the Human Assets Index (HAI) (see UN-CDP webpage on LDCs, and Guillaumont, 2009).
Keywords: I31; I32; 330